Menstruation in history. - Gomez, Pio Ivan; Pardo, Yaira Yohanna; Hernandez, Helena Patricia; Jimenez, Sandra Patricia; Pardo, Juan Carlos (Investigación y Educación en Enfermería, 2012)
Objective. To review historical constructs on menstruation. Methodology. Non-systematic review of the literature complemented with consultations with national academic authorities. Results. Menstruation is an experience that involves women and their social group, becoming a relevant event. Treatment of menstrual symptoms is linked to the cultural context in which it is developed. The menstruation experience varies according to popular beliefs, cultural characteristics, and information received to this respect within the social group where the woman is. Menstruation exceeds the imaginary that places it only within the feminine setting; It is a process that involves the social group, inasmuch as it has psycho-social and cultural implications. Conclusion. A relationship exists between menstruation, as a biological event, and the social processes per se, influenced by the historical beliefs that have been transmitted generation after generation.